A comparative study of psychological characteristics of national, state and district level shooters - Dhamale, S. G.; Bansode, N. (Journal of Interdisciplinary and Multidisciplinary Research, 2023)
Shooting is a target sport that comprises Rifle, Pistol, Trap, Skeet, and Running Target events for both men & women. They all use different guns and ammo. The main aim of the study is to give a comparison between national, state and district level shooters of Maharashtra state in terms of their psychological characteristics. The current research was involving 150 rifle shooters from Maharashtra. Players were divided into three groups based on their objectives: district (50), state (50), and national (50) rifle shooting players. In current study the psychological variables used such as self confidence, social adjustment, locus of control and self concept. The research concluded that district rifle shooting players are more self-assured than national and state rifle shooting players. National rifle shooting players are more socially adaptable in terms of emotional adjustment and social maturity than state and district rifle shooting players. In compared to state and district rifle shooting players, national players have a strong sense of self. State rifle shooting players have an average self concept, whereas district rifle shooting players have a low self concept.